2009
DOI: 10.3945/ajcn.2009.27474
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of a protein hydrolysate is accompanied by an accelerated in vivo digestion and absorption rate when compared with its intact protein

Abstract: Ingestion of a protein hydrolysate, as opposed to its intact protein, accelerates protein digestion and absorption from the gut, augments postprandial amino acid availability, and tends to increase the incorporation rate of dietary amino acids into skeletal muscle protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
272
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(289 citation statements)
references
References 38 publications
13
272
0
4
Order By: Relevance
“…Protein hydrolysates are commonly produced by adding proteolytic enzymes, resulting in a complex mixture of peptides with differing lengths, and free amino acids [12]. Hydrolysed casein may be more rapidly digested than intact casein [7,13,14]. Grimble and colleges found that hydrolysing whey proteins to mainly di-and tri-peptides improved absorption in the perfused human jejunum [15], however, other studies did not find any effect on absorption rates by hydrolysing whey proteins [13,16] or a slowed absorption rate [17].…”
Section: Introductionmentioning
confidence: 99%
“…Protein hydrolysates are commonly produced by adding proteolytic enzymes, resulting in a complex mixture of peptides with differing lengths, and free amino acids [12]. Hydrolysed casein may be more rapidly digested than intact casein [7,13,14]. Grimble and colleges found that hydrolysing whey proteins to mainly di-and tri-peptides improved absorption in the perfused human jejunum [15], however, other studies did not find any effect on absorption rates by hydrolysing whey proteins [13,16] or a slowed absorption rate [17].…”
Section: Introductionmentioning
confidence: 99%
“…As presented in previous works from our laboratory (Pennings et al 2011a, b;Pennings et al 2012;Koopman et al 2009a), we applied specifically produced intrinsically L-[1-…”
mentioning
confidence: 99%
“…The pre-dialytic parenteral nutrition seems to yield good results in order to preserve nutritional status (Cano et al, 1990), and it sounds to improve both morbidity and mortality on retrospective data (Capelli et al, 1994;Chertow et al, 1994). Others studies showed that the catabolism rate of AAs and net protein synthesis could be affected by the speed of protein digestion (Boirie et al, 1997, Koopman et al, 2009). Thus, soluble proteins of milk are more quickly oxidized and lead to a less efficience protein synthesis than casein.…”
Section: Present Dietary Approach To Treat the Patient With Chronic Rmentioning
confidence: 99%